I can't get no Satisfaction - Necessity Entrepreneurship and Procedural Utility - Joern Block; Philipp Koellinger (Tinbergen Institute, 2008)
We study a unique sample of 1,547 nascent entrepreneurs in Germany and analyze which factors are associated with their self-reported satisfaction regarding their start-up. Our study identifies a new facet of procedural utility and offers new insights about the motivations and goals of nascent entrepreneurs. Most importantly, we identify a group of nascent entrepreneurs that “cannot get satisfaction” with their start-up—not because their start-up fails to deliver financial returns, but because they did not choose to become entrepreneurs in the first place. This group of unsatisfied entrepreneurs includes individuals starting a business after a period of long-term unemployment and those individuals with a lack of better employment alternatives (necessity entrepreneurs). In addition, we provide additional evidence for the importance of both financial and non-financial incentives of entrepreneurs. While financial success is the most important determinant of start-up satisfaction, achievement of independence and creativity is also highly important. Our results emphasize the relevance of procedural utility for understanding economic behavior.
Keywords: J24; J17; L26; 330; Entrepreneurship; Satisfaction; Procedural Utility; Unemployment; Necessity Entrepreneurship; Entrepreneurship-Ansatz; Leistungsmotivation; Unternehmensgründung; Zufriedenheit; Arbeitslosigkeit; Deutschland